LITERATURE REVIEW : PERBANDINGAN EFEKTIVITAS PEMERIKSAAN KULTUR DAN POLYMERASE CHAIN REACTION (PCR) DALAM IDENTIFIKASI Neisseria gonorrhoeae PADA PASIEN GONORE - Sahira Rauf (Akademi Kesehatan John Paul II Pekanbaru, 2022)
Gonorrhea is a disease caused by the bacterium Neisseria gonorrhoea that generally attacks the genital mucosa or cervical mucosa. Gonorrhea has a higher incidence than other infectious diseases. The spread of this disease is higher in developing countries including Indonesia. Culture examination is the gold standard for the diagnosis of gonorrhea, this examination has good sensitivity and very high specificity, while the weakness is that it takes a long time to get positive results. Polymerase Chain Reaction (PCR) is an in vitro technique that can amplify a specific DNA section that lies between two known DNA sections. PCR is a biomolecular technique used for the isolation and exponential amplification of target DNA fragments or sequences through enzymatic replication, or without the use of living organisms. The PCR technique is faster than culture, effective, accurate, efficient, high sensitivity and specificity. This study aims to determine the effectiveness and differences in the results of culture and Polymerase Chain Reaction (PCR) in identifying Neisseria gonorrhoea in gonorrhea patients. This study used a literature review conducted by collecting library data based on PICO keywords using Google Scholar and PubMed databases. The results of the statistical test for sensitivity were 0.001 (p<0.05) and statistical specificity test was 0.095 (p>0.05). There was a significant difference in terms of sensitivity and there was no significant difference in terms of the specificity of the results of culture and Polymerase Chain Reaction (PCR) examinations.